RESOURCE DISTRIBUTION MODEL IN CLOUD ENVIRONMENTS - Ramil I. Khantimirov; Andrey A. Mikrukov (Открытое образование (Москва))
A new approach to distribution of load in computer clouds is proposed, based on the analysis of the equability of resource usage and resource usage forecast using intelligent algorithms.